To convert the equation from standard form to slope-intercept form (y = mx + b), let's start with the given equation:
\[ 11x - 8y = -48. \]
We can solve for \( y \) step by step:
-
Move the \( 11x \) term to the other side:
\[ -8y = -11x - 48. \]
-
Divide all terms by -8 to isolate \( y \):
\[ y = \frac{-11x}{-8} + \frac{-48}{-8}. \]
Simplifying that gives:
\[ y = \frac{11}{8}x + 6. \]
Now let's analyze the three responses:
- Bob's work resulted in \( y = 7.375 \), which does not correspond to the correct slope-intercept form.
- Bill's work gave \( y = \frac{11}{8}x + 6 \), which should have been correct, but let's check the equation.
- Bud's work resulted in \( y = -\frac{11}{8}x + 6 \), which is incorrect.
None of the responses given (Bob, Bill, Bud), are correct based on our calculations. The correct slope-intercept form should have been \( y = \frac{11}{8}x + 6 \).
Therefore, the answer is None of them are correct.